2-[1-(2-Hydroxy-3-methoxybenzyl)-1H-benzimidazol-2-yl]-6-methoxyphenol methanol 1.13-solvate - Al-Douh, Mohammed H.; Osman, Hasnah; Abd Hamid, Shafida; Kia, Reza; Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the main molecule of the title compound, C22H20N2O4·1.13CH4O, the dihedral angles between the benzimidazole plane and the two benzene rings are 80.53 (10) and 82.76 (10)°. The solvent molecules are disordered between three positions, with refined occupancies of 0.506 (13), 0.373 (13) and 0.249 (5). The crystal structure is stabilized by intermolecular O-HO, O-HN and C-HO hydrogen bonds. The crystal studied was a merohedral twin [BASF ratio of 0.917 (1)/0.083 (1)].